A novel indicator for predicting functional recovery in elderly hip fracture patients - Wu, Weicheng; Guo, Zhening; Zhu, Peiyao; Lv, Bo; Mao, Yongtao; She, Chang; Xu, Wei; Gu, Jun; Pan, Jie; Li, Liubing (Frontiers in Medicine, 2025)
BackgroundThe inflammatory response following hip fracture significantly influences postoperative functional recovery in patients. However, to date, no inflammatory index has been identified as a reliable and accurate predictor of functional recovery, especially in elderly patients with hip fractures. This study introduces and evaluates a novel inflammatory marker, the lymphocyte ratio-calcium index (LRCa3), for predicting one-year postoperative functional recovery and compares its performance to that of established markers, including the platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), systemic immune-inflammation index (SII), aggregate index of systemic inflammation (AISI), and systemic inflammation response index (SIRI).MethodsA retrospective analysis was conducted on 111 elderly patients (≥65 years) who underwent hip fracture surgery, and their demographic and laboratory data were analyzed. Patients were classified into good or poor recovery groups based on the Harris hip score (HHS) 1 year postoperatively. LRCa3 was calculated as the lymphocyte ratio multiplied by the cube of the serum calcium level. Logistic regression and receiver operating characteristic (ROC) curve analyses were performed to assess the predictive performance of the LRCa3 and other inflammatory indices. A nomogram prediction model was constructed.ResultsROC curve analysis revealed that, compared with the SII (AUC: 0.601), the SIRI (AUC: 0.61), the AISI (AUC: 0.577), and the MLR (AUC: 0.626) had superior predictive performance. Multivariate logistic regression revealed that the LRCa3 was an independent predictor of one-year functional recovery. The incorporation of LRCa3 into a nomogram further enhanced its predictive capacity, providing a more accurate tool for postoperative outcome assessment.ConclusionLRCa3 is a novel and effective biomarker for predicting postoperative functional recovery in elderly hip fracture patients. Its integration into clinical practice could facilitate individualized patient management and improve long-term outcomes.